Cocos2d-x game development blueprints : build a plethora of games for various genres using one of the most powerful game entines, Cocos2d-x /: build a plethora of games for various genres using one of the most powerful game entines, Cocos2d-x. (2015) - Sequeira, Karan
No abstract available